Development of lexical competence in the english language through a system of didactic exercises - Cuenca Cumbicos, Jaime Andres; Lalangui Sedamanos, Jhonny Paul (Machala, Utmachala, 2023)
This thesis is focused on encompassing the main problems present in the teaching-learning process of the English language in students of the fourth "A" of the basic education school "La Providencia" in relation to the development of lexical competence in vocabulary of this language. The research is carried out under the quantitative paradigm which allows responding to the needs posed through the use of theoretical level methods such as the synthetic analytical, historical logical and deductive hypothetical methods used for the construction of the theoretical framework and the analysis of the results obtained from the application of empirical methods such as observation and the diagnostic test, which allowed knowing the low level of lexical competence in vocabulary. Based on this, it is proposed how to contribute to the development of lexical competence in students of the subject of English, where pedagogical and didactic foundations are assumed that allow the implementation of different didactic methods and techniques both at a theoretical and empirical level. The intervention proposal is based on a system of didactic exercises characterized by integrating the lexical method as the main component. Finally, the results of the theoretical corroboration and the application of the system of exercises carried out in the educational institution are presented, which made it possible to assess its effectiveness.
La presente tesis se centra en abarcar los principales problemas presentes en el proceso de enseñanza - aprendizaje del idioma inglés en los estudiantes de cuarto año de la escuela de educación básica “La Providencia” en relación al desarrollo de la competencia léxica en vocabulario de este idioma. La investigación se efectúa bajo el paradigma cuantitativo el cual permite responder a las necesidades planteadas a través del uso de métodos de nivel teórico como el analítico sintético, histórico lógico y el hipotético deductivo empleados para la construcción del marco teórico y el análisis de los resultados obtenidos a partir de la aplicación de los métodos empíricos como la observación y la prueba diagnóstica, los cuales permitieron conocer el bajo nivel de competencia léxica en vocabulario. En función de eso, se propone como contribuir a desarrollar la competencia léxica en los estudiantes de la asignatura de inglés, donde se asumen fundamentos de tipo pedagógico y didáctico que permiten la implementación de distintos métodos y técnicas didácticos tanto de nivel teórico como empírico. La propuesta de intervención se basa en un sistema de ejercicios didácticos que se caracteriza por integrar el método lexical como principal componente. Por último, se presentan los resultados de la corroboración teórica y la aplicación del sistema de ejercicios llevado a cabo en la institución educativa, lo que posibilitó valorar su efectividad.
Keywords: COMPETENCIA LEXICA; VOCABULARIO; METODO DIDACTICO; PROCESO DE ENSEÑANZA-APRENDIZAJE